(untitled) (Research, Society and Development, 2022)
Atlantic forest fragmentation is considered a serious threat to biodiversity since this biome is considered the hottest hotspot. Due to this reason, many environmental strategies are being developed in order to support its, one of them being the prioritization of forest remnants using landscape ecology metrics. Thus, the main objective of this study is the development of a patches prioritization index (PPI) in order to support conservation actions and research. Firstly, a diagnosis of forest remnants in the study area was performed using landscape ecology metrics. Secondly, by literature review and expert consulting, were selected the adequate landscape ecology metrics, next, their importance was determined for PPI composition. Selected landscape metrics (AREA, SHAPE, and NEARD) composed the PPI. Finally, using a rapid ecological assessment (BII) the PPI was validated in the field. The results showed that the study area has patches able to aid biodiversity maintenance in the landscape. Further, the selection and importance attributed to landscape ecology metrics were demonstrated to be adequate. Also, the index is accurate enough to identify priority patches, classes, and regions for biodiversity conservation. Finally, the validation of PPI in the field showed that PPI is effective to estimate patches integrity in the field. In conclusion, our results suggest that PPI could be used for the prioritization of Atlantic forest remnants in a landscape covered mainly by Atlantic forest remnants and agriculture.